Impact of interacting bark structure and rainfall conditions on stemflow variability in a temperate beech-oak forest, central Germany. Issue 11 (17th August 2016) - Van Stan, John T.; Lewis, Elliott S.; Hildebrandt, Anke; Rebmann, Corinna; Friesen, Jan
ABSTRACT: Trees concentrate rainfall to near-stem soils via stemflow. When canopy structures are organized appropriately, stemflow can even induce preferential flow through soils, transporting nutrients to biogeochemically active areas. Bark structure significantly affects stemflow, yet bark-stemflow studies are primarily qualitative. We used a LaserBark to compute bark microrelief (MR), ridge-to-furrow amplitude ( R ) and slope ( S ) metrics per American Society of Mechanical Engineering standards (ASME-B46.1–2009) for two morphologically contrasting species ( Fagus sylvatica L. (European beech), Quercus robur L. (pendunculate oak)) under storm conditions with strong bark water storage capacity (BWSC) influence in central Germany. Smaller R and S for F. sylvatica significantly lowered BWSC, which strongly and inversely correlated to maximum funnelling ratios and permitted stemflow generation at lower rain magnitudes. Larger R and S values in Q. robur reduced funnelling, diminishing stemflow drainage for larger storms. Quercus robur funnelling and stemflow was more reliant on intermediate rain intensities and intermittency to maintain bark channel-dependent drainage pathways. Shelter provided by Q. robur 's ridged bark also appears to protect entrained water, lengthening mean intrastorm dry periods necessary to affect stemflow. Storm conditions where BWSC plays a major role in stemflow accounted for much of 2013's rainfall at the nearest meteorological station (Wulferstedt).Editor M.C. Acreman;Associate editor not assigned